A novel crystal form of metacetamol: the first example of a hydrated form. Issue 11 (4th October 2019) - Zemtsova, Viktoria M.; Fedorov, Alexey Yu.; Fedorova, Elizaveta A.; Boa, Callum; Arkhipov, Sergey G.; Rychkov, Denis A.; Minkov, Vasily S.; Pulham, Colin R.; Boldyreva, Elena V.
Abstract : The crystal structure and crystallization conditions of a novel form of metacetamol, the hemihydrate, are reported. Its crystal packing was analysed and compared with the packings of the two previously known polymorphs of metacetamol. Abstract : We report the crystal structure and crystallization conditions of a first hydrated form of metacetamol (a hemihydrate), C8 H9 NO2 ·0.5H2 O. It crystallizes from metacetamol‐saturated 1:1 ( v / v ) water–ethanol solutions in a monoclinic structure (space group P 21 / n ) and contains eight metacetamol and four water molecules per unit cell. The conformations of the molecules are the same as in polymorph II of metacetamol, which ensures the formation of hydrogen‐bonded dimers and R 2 2 (16) ring motifs in its crystal structure similar to those in polymorph II. Unlike in form II, however, these dimers in the hemihydrate are connected through water molecules into infinite hydrogen‐bonded molecular chains. Different chains are linked to each other by metacetamol–water and metacetamol–metacetamol hydrogen bonds, the latter type being also present in polymorph I. The overall noncovalent network of the hemihydrate is well developed and several types of hydrogen bonds are responsible for its formation.